Preclinical testing of a new radiofrequency ablation device in a porcine perianal fistula model - Sunseok Yoon; Jung-Woo Choi; Yongtaik Son; Hyun Soon Lee; Kwang Dae Hong (Annals of Coloproctology)
Purpose Anorectal fistulas present a treatment challenge, with conventional surgical methods potentially resulting in complications such as fecal incontinence. To improve patient outcomes, more effective and minimally invasive therapies are critically needed. In this study, an optimal porcine model for the creation of anorectal fistulas was developed and used to evaluate the efficacy of radiofrequency ablation (RFA) therapy. Methods Two distinct but related experiments were conducted. In the first experiment, a reliable and standardized porcine anorectal fistula model was developed. In the second, the healing process was assessed, and outcomes were compared between the RFA-treated group and the control group using the established porcine model. Results The results indicated that a 3.5-cm fistula tract length and a 14-day evaluation period following seton removal are optimal for the porcine anorectal fistula model. In the second experiment, the RFA group tended to exhibit better outcomes regarding fistula closure, although the differences were not statistically significant. Histopathologically, no significant difference in inflammation grade was observed between groups; however, scar tissue was more predominant in the RFA group. Conclusion The findings suggest that RFA therapy may offer potential benefits in the treatment of anorectal fistulas, as demonstrated using a porcine model. To validate these results and explore the mechanisms of action underlying RFA therapy for anorectal fistulas, further research involving larger sample sizes and a more robust study design is required.